2016
DOI: 10.1007/s11102-016-0727-0
|View full text |Cite
|
Sign up to set email alerts
|

Double separate versus contiguous pituitary adenomas: MRI features and endocrinological follow up

Abstract: Double contiguous pituitary adenomas are difficult to anticipate preoperatively or to resolve intraoperatively. Although double contiguous adenomas are much more common than double separate lesions, both have a risk for subtotal resection and, thus, residual mass and/or endocrinopathy may ensue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In our literature review, FGA co-occurring with lactotroph adenoma was not previously reported although our search generated 3 silent gonadotroph and lactotroph double adenoma cases ( Table 2 ). Roberts et al 7 presented 2 such cases; the first case was a 43-year-old woman who presented with amenorrhea and galactorrhea and had an elevated PRL level. Cabergoline treatment yielded a biochemical response without tumor size reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our literature review, FGA co-occurring with lactotroph adenoma was not previously reported although our search generated 3 silent gonadotroph and lactotroph double adenoma cases ( Table 2 ). Roberts et al 7 presented 2 such cases; the first case was a 43-year-old woman who presented with amenorrhea and galactorrhea and had an elevated PRL level. Cabergoline treatment yielded a biochemical response without tumor size reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Cabergoline treatment yielded a biochemical response without tumor size reduction. 7 The second case was a 56-year-old woman who presented with headaches. 7 Although the PRL level was not elevated, pathology reported an FSH/ASU staining–positive adenoma slightly intermingling with a PRL staining–positive adenoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…d-f After transsphenoidal surgery, T1-weighted with contrast sagittal, T1-weighted without contrast coronal, T2-weighted without contrast coronal views, respectively, tumor resection collision sellar lesion can only be determined by histological examination; therefore, preoperative diagnosis is quite difficult. Most case reports include a pituitary adenoma coexisting with either neoplastic, adenomatous, congenital, vascular, or inflammatory sellar lesions such as: another adenoma [5,6,12,13]; craniopharyngioma [14][15][16][17][18]; schwannoma [5]; hypophysitis [19,20]; arachnoid, colloid, and epidermoid cysts [21][22][23]; gangliocytoma [5,[24][25][26]; Rathke's cleft cyst [5,14,27]; neurosarcoidosis [5,28]; plasmacytoma [29]; chondroma [30]; lymphoma [31]; lung cancer metastasis [32]; and meningioma [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports of plurihormonal tumours have been a misinterpretation of either trapped non‐tumourous tissue or cross‐reactivities of antisera. A number of studies have reported double tumours arising in the adenohypophysis, and the use of transcription factors allows the clear distinction of these as separate lesions that should be distinguished from unusual plurihormonal neoplasms that would probably not respond to usual therapies. What remains to be shown is whether these are indicative of familial predisposition that is now recognized more widely in endocrine tumours, or whether they are simply a reflection of the common neoplastic triggers that remain unknown.…”
Section: Adenohypophysial Tumour Classification Based On Cytogenesismentioning
confidence: 99%